Graphene oxide and graphene quantum dots as delivery systems of cationic porphyrins: photo-antiproliferative activity evaluation towards T24 human bladder cancer cells - Menilli, Luca (2021)
The development of new photodynamic therapy (PDT) agents designed for bladder cancer (BC) treatments is of utmost importance to prevent its recurrence and progression towards more invasive forms. Here, three different porphyrinic photosensitizers (PS) (TMPyP, Zn-TMPyP, and P1-C5 ) were non-covalently loaded onto graphene oxide (GO) or graphene quantum dots (GQDs) in a one-step process. The cytotoxic effects of the free PS and of the corresponding hybrids were compared upon blue (BL) and red-light (RL) exposure on T24 human BC cells. In addition, intracellular reactive oxygen species (ROS) and singlet oxygen generation were measured. TMPyP and Zn-TMPyP showed higher efficiency under BL (IC50: 0.42 and 0.22 µm, respectively), while P1-C5 was more active under RL (IC50: 0.14 µm). In general, these PS could induce apoptotic cell death through lysosomes damage. The in vitro photosensitizing activity of the PS was not compromised after their immobilization onto graphene-based nanomaterials, with Zn-TMPyP@GQDs being the most promising hybrid system under RL (IC50: 0.37 µg/mL). Overall, our data confirm that GO and GQDs may represent valid platforms for PS delivery, without altering their performance for PDT on BC cells.